INTRADIALYTIC HYPOTENSION, QUALITY OF LIFE AND FIVE YEARS SURVIVAL IN DIALYSIS PATIENTS - Trajcheska, Lada; Mladenovska, Daniela; Selim, Gjuslen; Dzekova, Pavlina; Sikole, Aleksandar (Journal of Morphological Sciences; Vol 1 No 1 (2018): JMS, 2018)
Introduction : As complication of hemodialysis, Intradialytic Hypotension (IDH) is associated with risk for mortality. Those patients suffer from diminished Quality of life (QOL). The aim of this study was to compare the QOL and survival of two groups of dialysis patients, according to the presence of IDH. Methods: The prevalent population of 162 dialysis patients from one dialysis center, was divided according to the presence of IDH. Patients were scored for QOL with the standard SF 36 questionnaire at the start of the study. Results : The percentage of IDH was 26%.  Groups were not statistically different for participants age, dialysis vintage and presence of diabetes. QOL scores from all domains were substantially reduced in the IDH group of patients. The component scores for the physical and mental domains were nearly halved and statistically worse in IDH group of patients (p=0.0001, p=0.0001). In 60 months of follow up, in the IDH group 23 (55%) of patients died, and in the group without IDH 46 (38%). Kaplan Meier curves showed statistically better survival in the Non - IDH group, when compared to IDH group in months (47.67 Â± 1.98 vs. 39.74 Â± 3.40, p= 0.038), respectively. In Cox -Regression analysis patients with IDH had 1.68 higher risk of death with Confidential Interval of 1.021 â€“ 2.78, p= 0.041. Conclusion: IDH deteriorates the QOL and life expectancy in dialysis patients. Interventions are needed on modifiable factors affecting IDH in order to achieve better outcomes.